The Catalogue of Vascular Plants of the Southern Cone and the Flora of Argentina: their contribution to the World Flora - Zuloaga, Fernando Omar (2015)
The checklist of the vascular plants of the Southern Cone presents updated information of 19,787 taxa and 44,943 synonyms, distributed in 2,679 genera and 318 families. This checklist was prepared, and its permanently updated, using the database "Documenta Florae Australis", with the contribution of numerous researchers and institutions, and constitutes the bases for the Flora of Argentina, currently under preparation. Here we evaluate the current knowledge of vascular plants in the Southern Cone and provide a summary of the ongoing Flora of Argentina, and the significance of these projects for the World Flora on line and to the botanical studies in the region.